Question about Dell Optiplex GX280 (99301) Motherboard

Ad

POST ("power on self test") codes for the Dell GX280 are in a format of n-n-n as in 3-1-2. This would sound like 3 beeps, followed by 1 beep and finally 2 beeps. If you're not paying attention, that 3-1-2 beep code could sound like 6 simple beeps.

Dell has a page for the GX280 dedicated to Troubleshooting Tools and Utilities. There's a great deal of information on it - but the POST codes you're looking for are explained in detail about mid-way down under "Beep Codes" This document and associated links should go a long way to help you properly diagnose the problem with your GX280.

Please take a minute to rate this reply if it was helpful to you. Good luck!

Posted on Aug 02, 2010

Ad

Hi there,

Save hours of searching online or wasting money on unnecessary repairs by talking to a 6YA Expert who can help you resolve this issue over the phone in a minute or two.

Best thing about this new service is that you are never placed on hold and get to talk to real repairmen in the US.

Here's a link to this great service

Good luck!

Posted on Jan 02, 2017

Ad

10+10+10=30, 10+6+6=22, 6-3+3=0, 6x(3+10)=
78

Oct 25, 2016 | Office Equipment & Supplies

x=-2

If you're asking how to do this on a particular calculator, please specify the make and mode. If this is homework, be sure to show your work.

If you're asking how to do this on a particular calculator, please specify the make and mode. If this is homework, be sure to show your work.

Feb 08, 2014 | Office Equipment & Supplies

For 3x(7x+6x)=0, x=0

For 3x(7x+6x)=1, x=1/39

For 3x(7x+6x)=2, x=2/39

For 3x(7x+6x)=3, x=3/39 or 1/13

For 3x(7x+6x)=4, x=4/39

And so on...

For 3x(7x+6x)=1, x=1/39

For 3x(7x+6x)=2, x=2/39

For 3x(7x+6x)=3, x=3/39 or 1/13

For 3x(7x+6x)=4, x=4/39

And so on...

Jun 22, 2011 | Acer Aspire One Netbook

you have to make sure you are using the correct format for your drive i.e (+/-)

8X DVD-Super Multi double-layer drive:

- Read: 24X CD-ROM, 24X CD-R, 24X CD-RW, 8X DVD-ROM, 8X DVD-R, 8X DVD+R, 8X DVD-ROM DL (double-layer), 6X DVD-R DL (double-layer), 6X DVD+R DL (double-layer), 8X DVD-RW, 8X DVD+RW, 5X DVD-RAM, 4X BD-ROM, 4X BD-R, 2X BD-RE, 4X BD-ROM DL (double-layer), 4X BD-R DL (double-layer), 2X BD-RE DL (double-layer)
- Write: 24X CD-R, 16X CD-RW, 8X DVD-R, 8X DVD+R, 6X DVD-RW, 6X DVD+RW, 5X DVD-RAM, 4X DVD+R DL (double-layer), 4X DVD-R DL (double-layer)

8X DVD-Super Multi double-layer drive:

- Read: 24X CD-ROM, 24X CD-R, 24X CD-RW, 8X DVD-ROM, 8X DVD-R, 8X DVD+R, 6X DVD-ROM DL (double-layer), 6X DVD-R DL (double-layer), 6X DVD+R DL (double-layer), 8X DVD-RW, 8X DVD+RW, 5X DVD-RAM
- Write: 24X CD-R, 24X CD-RW, 8X DVD-R, 8X DVD+R, 6X DVD-R DL (double-layer), 6X DVD+R DL (double-layer), 6X DVD-RW, 8X DVD+RW, 5X DVD-RAM

Apr 09, 2011 | Acer Computers & Internet

(2x - 3y)(3x + 2y) = 2x*3x + 2x*2y - 3y*3x - 3y*2y

= 6x^2 + 4xy - 9xy - 6y^2

= 6x^2 - 5xy - 6y^2 You multiply each element in the first set of brackets by each element in the second set of brackets and then consolidate like terms and arrange them in sequence of powers, first x and then y. So:

2x by 3x = 6x squared

2x by 2y = 4xy

-3y by 3x = -9xy

-3y by 2y = 6y squared

6x squared -5xy + 6y squared

= 6x^2 + 4xy - 9xy - 6y^2

= 6x^2 - 5xy - 6y^2 You multiply each element in the first set of brackets by each element in the second set of brackets and then consolidate like terms and arrange them in sequence of powers, first x and then y. So:

2x by 3x = 6x squared

2x by 2y = 4xy

-3y by 3x = -9xy

-3y by 2y = 6y squared

6x squared -5xy + 6y squared

Dec 04, 2010 | Yahoo Computers & Internet

The first step here is to draw a rough sketch of the two curves, and find the two points they meet. If you set x^3-6x^2+8x = x^3-4x, then you can rearrange this into the quadratic equation 6x^2-12x = 0. Solving this tells you x=0 or 2 : these are the two x values where the curves meet, and they give the bounds on your integral.

When you sketch the curves, you'll see that x^3-4x is below x^3-6x^2+8x, so the thing you need to integrate is (x^3-6x^2+8x)-(x^3-4x), that is, 12x-6x^2. If you integrate this from 0 to 2, you'll have the answer you need!

When you sketch the curves, you'll see that x^3-4x is below x^3-6x^2+8x, so the thing you need to integrate is (x^3-6x^2+8x)-(x^3-4x), that is, 12x-6x^2. If you integrate this from 0 to 2, you'll have the answer you need!

May 27, 2010 | Computers & Internet

Conventional/Extended memory failure

Mar 04, 2010 | ASUS P6T Deluxe V2, LGA1366, Triple...

6x+5(x+9y)+7y

6x+5x+45y+7y <- Distributive property of multiplication

11x+52y < - Simplify

11x+52y - Simplified version

Further learning:

Distributive property of multiplication:

http://www.math.unt.edu/mathlab/emathlab/distributive_property_of_multipl.htm

6x+5x+45y+7y <- Distributive property of multiplication

11x+52y < - Simplify

11x+52y - Simplified version

Further learning:

Distributive property of multiplication:

http://www.math.unt.edu/mathlab/emathlab/distributive_property_of_multipl.htm

Nov 21, 2009 | Video Game Consoles & Games

6x- 3 = y; (0, -3)

Here 6x - 3 = y is the equation

The ordered pair is (0, -3 )

It means if you substitutes 0 for x and -3 for y the equation will be true

Let us substitute and see:-

'6x' (means 6 times x) means 6 times 0 which is equal to 0

So the equation 6x - 3 = y becomes

0- 3 = -3 is correct

The ordered pair means the values of x and y which make the equation correct

Hope this is clear enough

Good luck

luciana44

Here 6x - 3 = y is the equation

The ordered pair is (0, -3 )

It means if you substitutes 0 for x and -3 for y the equation will be true

Let us substitute and see:-

'6x' (means 6 times x) means 6 times 0 which is equal to 0

So the equation 6x - 3 = y becomes

0- 3 = -3 is correct

The ordered pair means the values of x and y which make the equation correct

Hope this is clear enough

Good luck

luciana44

Sep 27, 2009 | The Learning Company Achieve! Math &...

6x+6=4x+12

Since 4x contains the variable to solve for, move it to the left-hand side of the equation by subtracting 4x from both sides.

6x+6-4x=12

Since 6x and -4x are like terms, add -4x to 6x to get 2x.

2x+6=12

Since 6 does not contain the variable to solve for, move it to the right-hand side of the equation by subtracting 6 from both sides.

2x=-6+12

Add 12 to -6 to get 6.

2x=6

Divide each term in the equation by 2.

(2x)/(2)=(6)/(2)

Simplify the left-hand side of the equation by canceling the common factors.

x=(6)/(2)

Simplify the right-hand side of the equation by simplifying each term.

x=3

Good Luck

Since 4x contains the variable to solve for, move it to the left-hand side of the equation by subtracting 4x from both sides.

6x+6-4x=12

Since 6x and -4x are like terms, add -4x to 6x to get 2x.

2x+6=12

Since 6 does not contain the variable to solve for, move it to the right-hand side of the equation by subtracting 6 from both sides.

2x=-6+12

Add 12 to -6 to get 6.

2x=6

Divide each term in the equation by 2.

(2x)/(2)=(6)/(2)

Simplify the left-hand side of the equation by canceling the common factors.

x=(6)/(2)

Simplify the right-hand side of the equation by simplifying each term.

x=3

Good Luck

Sep 10, 2009 | Audio Players & Recorders

488 people viewed this question

Usually answered in minutes!

×